Gender difference in utilization willingness of institutional care among the single seniors: evidence from rural Shandong, China - Yangyang Qian; Jie Chu; Dandan Ge; Li Zhang; Long Sun; Chengchao Zhou (BMC, 2017)
Abstract Background Institutional care has become an urgent issue in rural China. Rural single seniors, compared with their counterparts, have lower income and are more vulnerable. Gender is also a significant factor determining long-term institutional care. This study is designed to examine the gender difference towards utilization willingness of institutional care among rural single seniors. Methods A total of 505 rural single seniors were included in the analysis. Binary logistic regression model was used to examine the gender difference towards utilization willingness for institutional care, and also to identify the determinants of the utilization willingness for institutional care among rural single male and female seniors. Results Our study found that about 5.7% rural single seniors had willingness for institutional care in Shandong, China. Single females were found to be less willing for institutional care than single males in rural areas (OR = 0.19; 95 CI 0.06-0.57). It's also found that psychological stress was associated with institutionalization willingness in both single males (P = 0.045) and single females (P = 0.013) in rural China. The rural single seniors who lived alone were found to be more willing for institutional care both in males (P = 0.032) and females (P = 0.002) compared with those who lived with children or others. Conclusions This study found that there was a gender difference towards utilization willingness for institutional care among single seniors in rural China. Factors including psychological stress and living arrangements were determinants of institutionalization willingness both in single males and females. Targeted policies should be made for rural single seniors of different gender.